Efektivitas Pijat dalam Mengurangi Nyeri pada Kala I Persalinan - Octa Dwienda R; Miratu Megasari; Novita Lusiana Sarmin (Jurnal Kesehatan Komunitas, 2015)
Massage is a technique that can relieve pain by blocking the pain signals, increasing blood circulation and oxygenation to the entire tissue. Pregnant women who receive 20 minutes massage during maternity process will be free from pain. The purpose of this study is to determine the effectiveness of massage in order to reduce pain at the stage of delivery process for pregnant women This research is a quasi-experiment approach using pre-post test research design. The research location was at BPS Ernita Pekanbaru and conducted in April-June 2014. The number of sample in this study was 30 people with purposive sampling technique. This study is applied primary data which were analyzed by Paired Sample T-Test (Dependent T-Test) with the degree of Î± = 0.05. The result showed that the average pain scale without receiving a massage was 8.67 and decreasing after pregnant women receive a massage to 5.33. Furthermore, average pain scale without pain killer was 9.47 and after drug administration was 3.07. In other words, massage and medication was effective methods in order to reduce pain with p value : 0.001 To conclude, a massage is quite effective method in reducing pain for pregnant women during her first phase of maternity.